Evaluation Analysis of Employee Performance to Enhance Work Quality: A Case Study at the Secretariat of the General Election Commission in Gunungsitoli City - Yasaro Dotonafo Laoli; Eliyunus Waruwu; Yupiter Mendrofa; Forman Halawa (Yayasan Riset dan Pengembangan Intelektual, 2024)
Quality human resources (HR) play a crucial role in advancing organizations, especially amidst competitive environments striving for superior performance. Regular performance evaluation by management assesses employees' adherence to responsibilities, legal compliance, and ethical conduct. The evaluation aims to enhance work quality, foster a safe environment, boost motivation and satisfaction, improve efficiency, productivity, and overall performance. This qualitative descriptive study investigates employee performance evaluation at the Gunungsitoli City KPU Secretariat, focusing on improving discipline, responsibility, and HR quality. Findings indicate effective evaluation processes influenced by factors such as ability, motivation, and attitude.